2016
DOI: 10.1016/j.vaccine.2016.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events following HPV vaccination, Alberta 2006–2014

Abstract: Rates of AEFI after HPV immunization in Alberta are low and consistent with types of events seen elsewhere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 12 publications
2
13
0
1
Order By: Relevance
“…Epidemiological studies conducted globally since the launch of the HPV vaccines have failed to find any increased risk of developing conditions claimed to be associated with the vaccine such as complex regional pain syndrome (CRPS) [10] , [11] , postural orthostatic tachycardia syndrome (POTS) [11] , multiple sclerosis or other demyelinating diseases [12] , venous thromboembolism [13] , or any other adverse events following immunization [14] . A meta-analysis [15] and a recent review [16] found that both the bi- and quadrivalent HPV vaccines were safe.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies conducted globally since the launch of the HPV vaccines have failed to find any increased risk of developing conditions claimed to be associated with the vaccine such as complex regional pain syndrome (CRPS) [10] , [11] , postural orthostatic tachycardia syndrome (POTS) [11] , multiple sclerosis or other demyelinating diseases [12] , venous thromboembolism [13] , or any other adverse events following immunization [14] . A meta-analysis [15] and a recent review [16] found that both the bi- and quadrivalent HPV vaccines were safe.…”
Section: Introductionmentioning
confidence: 99%
“…Several possibilities can be offered to address this problem. For instance, reminder/recall systems can help to identify the cross-border child, the system could allow their citizens to update their own information 108 or an IIS interconnected with civil registries could reduce this bias. 157 Timeliness is another aspect that should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…94 Another example of IIS connected to AEFI surveillance system is the Alberta IIS, where AEFIs related to HPV vaccination were explored. 108 Among 195,270 women who received the vaccine, only 192 reported AEFIs. They were also able to know the type of AEFI reported, how many days after the immunization, associated dose, if hospitalization was required and the outcome.…”
Section: Possibility To Record Aefimentioning
confidence: 99%
“…The prevalence of HPV infection and cervical cancer is significantly higher [ 11 – 23 ] and HPV vaccination rates lower among Indigenous peoples [ 23 ]. This inequity exists despite the availability of vaccines with demonstrated safety profiles and efficacy, and funded vaccination programs [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccines preventing HPV infection demonstrate long-term effectiveness and acceptable safety profiles [ 24 ]. However, a number of issues specific to the HPV vaccine influence its acceptability and uptake in the general population; these factors are well described in systematic reviews [ 25 , 26 , 57 61 ] and include knowledge and perceived risk of HPV disease, misinformation about vaccine safety, cost, misperceptions that the vaccine induces sexual promiscuity, and multi-dose vaccine series delivery. Additional challenges in the school setting include the information and consent process, vaccination setting, and student anxiety regarding privacy and pain during vaccination [ 62 ].…”
Section: Introductionmentioning
confidence: 99%